Strategy of Ethnic Identity Negotiations of Javanese Migrants Adolescents in Family Interaction - Aryanti, Nina Yudha (KOMUNITAS: International Journal of Indonesian Society and Culture, 2017)
This article seeks to discuss the strategies of negotiation of Javanese ethnic identity in families among Javanese migrants in Lampung. The study found that there are three ways where the adolescents of Javanese migrants negotiate their ethnic identity. First, the adolescent states Javanese ethnic identity as a positive identity safely at family interaction. Second,they state Javanese ethnic identity as a single identity negatively in an unsafe situation. This happens when the adolescent avoid another ethnic identity that directed to them based on labeling in the family. Third, the adolescent choose one of two ethnic identities in a positive way. It’s referring to parent’s ethnic identity differences. Further, they use Javanese and non Javanese language at their family interaction as a basis for selecting ethnic identity.